Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
(1,75+1 1/6) : 7=(1 3/4+1 1/6):7=(1 9/12+1 2/12):7=2 11/12:7=35/12:7=35/12*1/7=5/12
2,3+0,7/0,7=2,3+1=3,3
4/3-(-1 1/3)^2:0,9=4/3-(4/3)^2:0,9=4/3 -16/9 :9/10=4/3 -16/9*10/9=4/3 -160/81=108/81 -160/81= -52/81
______________
3√7×2√5=6√35
(6√3)²=36×3=108
(1,75+1 1/6) : 7= (1 3/4 + 1 1/6) : 7 = (1 9/12 + 1 2/12) : 7 = 2 11/12 : 7 = 5/22
2,3+0,7/0,7= 2,3 + 0,7 : 0,7 = 2,3 + 1 = 3,3
4/3-(-1 1/3)^2:0,9= 4/3 - (-4/3)² : 9/10 = 4/3 - 16/9 : 9/10 = 4/3 - 16/9 x 10/9 = 4/3 - 160/81 = 108/81 - 160/81 = -52/81
Ostatniego zadania o pierwiastkach nie umiem wykonać, liczę na naj :))
Szczegółowe wyjaśnienie: